Advecção de nebulosidade rasa sobre o sul do Brasil devido a atuação do anticiclone transiente na confluência Brasil-Malvinas - Kaufmann, Thomas (2011)
Advections of shallow cloudiness from ocean toward the continent are often observed after the cold fronts and extratropical cyclones on the Southern South America. Such a process has characteristic persistence of 1-2 days and it may last for periods longer than 3 consecutive days. This study identified 108 cases over the Southern Brazil between 2005 and 2010, which were characterized using NCEP/NCAR reanalysis. A seasonal climatology determined that the higher frequencies of cases were in autumn and summer, and the lower frequencies in spring and winter. The average wind directions that occurred over the Southern Brazil (Southwesterly, Southerly, Southeasterly and Easterly) were due to positioning of the center of the transient anticyclone over three major regions. Based on these results, it was obtained three synoptic patterns at lower and middle-higher levels. A seasonal distribution of those three patterns was also performed. In such mean situations, it was remarkable the displacement of cold air from the Region of Brazil-Malvinas Confluence (BMC) toward the Southern Brazil due to the circulation of the transient high. Along the way, the stable flow suffers low levels instability due to turbulent mixing processes, and heat and moisture fluxes when it passes from cold to warm waters on the BMC. As a consequence, a shallow convection layer develops downstream in the flow with wide support for the formation of stratiform and/or cumuliform cloud cover as it top. The synoptic patterns show the large scale air subsidence as an inhibiting mechanism for the development of a deep convective layer. Still, the cloud cover was enough to generate low intensity precipitation and/or drizzle over the Southern Brazil. The analysis of the precipitating cases showed that the phenomenon affected the coastal zone more frequently, and, sometimes, the inland areas. Mean vertical profiles of the 108 events, and peculiarly the precipitating ones, indicated the presence of a thick dry layer at the middle and upper levels, and a shallow moist layer at lower levels (1000-700 hPa). This study showed the importance of the Region BMC for the regional weather and climate patterns. It is shown that the circulation induced by transient anticyclone is essential for the transport of cold air from the cold to the warm waters in Confluence zone, generating and advecting shallow cloudiness and an unstable moist boundary layer over the South of Brazil.